OXIDATIVE STRESS STATUS IN SERUM OF MIGRAINEURS IN ERBIL CITY-IRAQ - Rasoul, Abdulrahman Aziz (Journal of Sulaimani Medical College, 2025)
Background Migraine is one of the neurological disorders whose etiology remains elusive. Increased oxidative stress may be associated with migraine. Oxidative stress may play an important role in patients with migraine, and it can reflect the ability of tissues to free radical damage. Objectives To determine the oxidative stress markers levels in migraine patients’ serum. This study also included the use of oxidative stress indicators to diagnose migraines. Materials and Methods A total of 180 subjects (100 migraines and 80 healthy controls) were included in the study; nitric oxide (NO) metabolites, malondialdehyde (MDA), and superoxide dismutase (SOD) were measured in serum. Results In migraineurs, the levels of SOD, NO, and MDA were significantly higher when compared to healthy controls. There was a significant positive correlation between NO with MDA and SOD. Roc curve showed that NO was a useful marker for the diagnosis of migraine. Binary logistic regression documented that NO was negatively affect the life of migraineurs. Conclusion Therefore, oxidative stress has a role in the pathophysiology of migraine, and NO may serve as a useful diagnostic marker in migraine patients.
Keywords: Malondialdehyde migraine nitric oxide oxidative stress and superoxide dismutase